COMPARISON OF PERSONALITY TRAITS ON HEALTH AND SOCIAL SCIENCES STUDY PROGRAMS IN OLD AGED GROUPS - Setiawan Setiawan; Elvine Gunawan; Hanna Goenawan; Nova Sylviana; Teddy Hidayat; Ambrosius Purba (PAIFORI, 2021)
Personality is most commonly divided into five big traits1,2,3,4 namely Agreeableness, Conscientiousness, Extraversion, Neuroticism, and Openness to Experience. Agreeableness refers to the tendency to get along well with others and is associated with altruism or modesty. Conscientiousness refers to the extent to which an individual is careful, reliable, and persevering. Extraversion refers to the tendency to experience positive emotions and to have a positive outlook on life. In general, extroverts are talkative, sociable, outgoing, enthusiastic, and energetic. Neuroticism refers to the tendency to experience negative emotional states including anxiety, depression, or anger. Openness to experience refers to the tendency to be open-minded, imaginative, and curious. This study was cross-sectionall research with big five inventory (BFI) questionnaire. We used bahasa to validate translation of the BFI. The Participant N= 50 persons from health sciences and N= 116 persons from social science. All participant were lecturers and professors with aged interval 41-90 years. This questionnaire has 5 scale with 5 Likert scale mark with disagree strongly and agree strongly answer. The result showed all participant were included for three domain personality traits dimensions, which are agreeableness with 35, openness with 52, and conscientiousness with 29. Taken all together we concluded all lecturer and professors had tendency of agreeableness, openness, and conscientiousness for their personality traits dimensions.